Lições da racionalidade aberta: via para (re)criar as humanidades na complexidade cibercultural - Carvalho, Geovânia Nunes de (2024)
This research was developed based on the consideration of the onto-epistemic ethos of technoscience being a driver of the reduction and impoverishment of the humanities, in the cybercultural panorama of the 21st century heightened by Digital Information and Communication Technologies (DICT). Faced with this tension, I defended the thesis that the lessons of open rationality will be able to (re)create the humanities through their communicative attitudes, aiming to restore the multidimensional richness of homo complexus. I present a possible answer to the research question “How can open rationality be a path to the (re)creation of the humanities in the universe of Cybercultural Complexity?”, reaching the conclusion in the historical context that the lessons, in addition to being epistemic attitudes, are also moral. Keeping the consideration of historical development, I presented a possible interpretation and understanding of the phenomenon of Cybercultural Complexity, an overview of emergencies tensioned between technoscience and humanities. In defense of the arguments, I appropriated the referential trunk of Edgar Morin’s complexity and a list of experts, to compose the methodological paths freed from epistemic cages, assuming the creation of a complex ontoparadigmatic-epistemic-methodological dimension, in which I spliced patches of Gadamerian hermeneutics, other rigor, self-narrative and art through its poetic language and the comprehensive appropriation of cinematic characters. These complex philosophical paths were guides to elaborate the structuring elements, from a qualitative and bibliographic perspective, to (re)discuss, (re)interpret and understand the patches and amendments of a spiraling mutant reality.